Phonological variation of Java language in Kebumen district - Ambar Pujiyatno (English, 2017)
Geographically, Kebumen regency is a border area of ​​Javanese dialect Banyumas (ngapak) and Yogyakarta dialect (bandek). Language speakers in this region have their own language phenomenon. The purpose of this research is to describe phonological variation of Javanese language in Kebumen district. These variations include vowel sounds and consonant sounds, as well as other sound variations. To obtain the necessary data, the researcher used interview, record, and introspection techniques. Interviews were based on a gloss list provided to speakers of the language. The researchers recorded the interview. In addition, researchers also directly record the process of speaking of the speakers directly. The technique of introspections was done because researchers are speakers of language in Kebumen district. The analysis was done by comparing the Java language in Kebumen district with the standard Java language. The results obtained from this study showed that based on the residence, speakers and the social groups of Javanese speakers in Kebumen District have variations of vowel phoneme / a /, / i /, / u /, / e /, / o /, and consonant / b /, / d /, / k /, / g /, as well as variations of sound [r], [h], [-əw-], and [-ək]. The result of variation obtained is phoneme / a / pronounced [a], [ɔ], [ə], and [ɛ]. The phoneme / i / is pronounced [i], [I], and [ɛ]. The phoneme / u / is pronounced [u], and [U]. The phoneme / e / is pronounced [e] and [ɛ]. The phoneme / o / is pronounced [o] and [ɔ]. For the phoneme / b /, / d /, / g /, and / k / pronounced fixed as [b], [d], [g], and [k] which in standard Java is pronounced [p], [t] , [k], and [?]. The phoneme / r / can be inserted in the word. Phoneme / h / uninstalled. In addition, the sounds [-əw-] and [-ək] respectively as variants of the [-uw-] and [-a?] Sounds.